1974
DOI: 10.1136/bjo.58.5.536
|View full text |Cite
|
Sign up to set email alerts
|

Familial glaucoma. In nine generations of a South Hampshire family.

Abstract: A. Zorab (1932) reported a family suffering from "glaucoma simplex familialis" over three generations, the inheritance being autosomal dominant. Over the last 40 years, the various branches of this family have increased in number and two further generations have been added. In addition, four affected generations before those reported by A. Zorab (which he did not know about) have now been discovered. The purpose of this paper is to report the full extent of the pedigree of this family as far as is now known, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

1977
1977
2009
2009

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 4 publications
1
7
0
1
Order By: Relevance
“…Studies of pedigrees with iris hypoplasia in addition to juvenile/early onset autosomal dominant glaucoma, similar to those previously described by other authors,23 24 have failed to show linkage to 1q21-q31, suggesting a genetic as well as phenotypic difference 5677 Recently, two autosomal dominant pedigrees with features of iris hypoplasia, goniodysgenesis, and juvenile glaucoma, termed the iridogoniodysgenesis anomaly, were mapped to an 8.3 cM region on chromosome 6, 6p25 78.…”
Section: Genetics Of J-poagsupporting
confidence: 64%
“…Studies of pedigrees with iris hypoplasia in addition to juvenile/early onset autosomal dominant glaucoma, similar to those previously described by other authors,23 24 have failed to show linkage to 1q21-q31, suggesting a genetic as well as phenotypic difference 5677 Recently, two autosomal dominant pedigrees with features of iris hypoplasia, goniodysgenesis, and juvenile glaucoma, termed the iridogoniodysgenesis anomaly, were mapped to an 8.3 cM region on chromosome 6, 6p25 78.…”
Section: Genetics Of J-poagsupporting
confidence: 64%
“…172 Early studies had found genetic linkage of iris hypoplasia to the Rieger's syndrome locus at 4q25, 173 but others considered this association inconsistent. 174 A recent comprehensive review of the literature identifies a total of three causative loci (4q25, 6p25, and 13q14) and persuasively argues for retaining the broader clinical term 'AxenfeldRieger syndrome' to embrace a wide range of phenotypic subtypes (viz., Axenfeld anomaly, Rieger anomaly, Rieger syndrome, iridogoniodysgenesis anomaly, iridogoniodysgenesis syndrome, iris hypoplasia, and familial glaucoma iridogoniodysplasia).…”
Section: Glaucoma Associated With Other Congenital Anomalies Familialmentioning
confidence: 99%
“…It is transmitted as an autosomal dominant trait with complete penetrance. A number of families worldwide have been reported with this condition (Courtney and Hill 1931;Berg 1932;Stokes 1940;Hambresin and Schepens 1946;McCulloch and MacRae 1950; Martin and Zorab 1974). Affected individuals have a distinctive appearance of the irides.…”
Section: Introductionmentioning
confidence: 99%